Reintroduction of Cow’s Milk in Milk-Allergic Children - Nicolaou, Nicolaos; Tsabouri, Sophia; N. Priftis, Kostas (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2014)
Even though cow’s milk protein allergy (CMPA) is one of the most common food allergies in childhood, its prognosis is generally good and cow’s milk (CM) is usually reintroduced in the patient’s diet. The natural history of CMPA shows heterogeneity and is closely related to the immunological and clinical phenotype by which CMPA presents. Children with non-IgE-mediated CMPA tend to develop tolerance at an earlier age and at a higher percentage compared to those with IgE-mediated disease. In subjects with severe symptoms CMPA may persist for longer or ever. Although, the majority of children will outgrow their allergy, the individual timing of tolerance acquisition is largely unknown. Most of the current guidelines on the diagnosis and management of CMPA suggest reevaluation of milk- allergic children every 6- 12 months, and reintroduction of CM after a negative Oral Food Challenge (OFC). However, OFC procedure is time consuming, expensive and not without risk. Clinical variables and the measurements of sIgE levels and SPT wheal sizes to crude (whole) CM protein and individual milk protein components may provide some useful prognostic information in the course of CMPA. However, no clear-cut clinical or laboratory criteria exist to predict which children and at what age are more likely to pass a repeat (reintroduction) OFC. The identification of factors that could accurately predict the outcome of reintroduction OFC and the timing of tolerance development would be extremely useful in daily clinical practice. Until recently, reintroduction of CM was commonly attempted when children with CMPA were more likely to have become tolerant. Over the last years, a different approach in the management of milk and egg allergy has emerged with specific oral tolerance induction (SOTI) as a promising method for the treatment of food allergies. Furthermore, a number of studies have shown evidence that introduction of heated milk and egg protein into the diet of allergic patients may induce the acquisition of tolerance. Still, the question of when and how to reintroduce cow’s milk in milk-allergic children remains challenging and further research in this important field is necessary to provide both clinicians and anxious parents with the desirable answer.
Keywords: cow’s milk protein allergy